Interactive effects of water temperature and stoichiometric food quality on Daphnia pulicaria. (16th October 2020) - Starke, Cody W. E.; Jones, Catriona L. C.; Burr, Wesley S.; Frost, Paul C.
Abstract: While water temperatures vary widely within and among lakes, most studies of food quality on lake zooplankton have been conducted across a relatively narrow temperature range. Given the strong links between food, temperature, and metabolism, there is a need to assess the interactive effects of water temperature and food quality on the life history and population growth rates of zooplankton. This study examined Daphnia pulicaria life history and population growth rates exposed to variable food P content (molar C:P ratios c . 100–900) across a range of temperatures ( c . 12–30°C). Mass‐specific growth rate experiments were conducted for a period of 5 days, while Daphnia reproduction and survival metrics were measured for 28 days. Mass‐specific growth rates of D. pulicaria varied with food‐quality but the size of this effect depended on temperature. We observed a thermal limit of 28°C above which mortality reached 100%, while survival between 25 and 28°C was substantially reduced, after c . 20 days, in animals consuming food C:P ratios of 100. Poorer quality food (C:P 300–700) altered these temperature effects and increased the probability of survival in animals exposed to 25–28°C temperatures. When we examined the population‐level effects of these treatments, we found a rise in intrinsic rate with temperature with higher quality food, driven by an earlier age of first reproduction and shorter generation time. However, this increased population growth with temperature was not observed in animals consuming food with low P content. Altogether, we found strong interactive effects of temperature and food quality on Daphnia, with especially dynamic changes seen among differentially nourished animals raised in water above 25°C. These results demonstrate the complex non‐additive interactions of food quality and temperature responses in freshwater invertebrates and indicate that the effects of warming temperatures on zooplankton communities must be considered within the context of the animals' nutrition and metabolism if monitoring and mitigation efforts are to be successful.